Suomenoppijoiden käsityksiä kolmaspersoonaisten pronominien käytöstä ja puhuttelusta - Jokela Hanna (Finland, 2025)
My study is a survey that examines how Finnish as a second language speakers understand the use of Finnish pronouns and how to address people. I focus on the informants’ experiences and perspectives with the allocation of the Finnish third-person singular pronouns hän (‘he’ and ‘she’) and se (‘it’) and second-person singular sinä (familiar ‘you’) and plural te used as singular (formal ‘you’). I examine these issues particularly in light of previous studies carried out on addressing and variation. The informants in this study encompass a group of immigrants with an academic background. The survey shows that these informants can identify factors and situational variation that lead to pronoun choice as well as using the familiar or formal ‘you’. In examining hän and se, the differentiation between colloquial Finnish practices and the norms of standard Finnish is an important aspect. In particular, se is seen as confusing, as it is colloquially used for human beings and standardly for animals, while hän could also be used for household pets. The informants’ experiences with sinä and te show that they perceive their set of politeness norms used for addressing as one that often differs from that of a Finn.
My materials provide preliminary indications of the fact that the approach non-native speakers take on the deviation from standard Finnish norms and on situational variation may differ from that of native Finnish speakers. What is interesting is that identifying variation does not necessarily change one’s own approach or way of speaking.